CLINICAL USE OF TRABECULAR BONE SCORE FOR THE DIAGNOSIS OF OSTEOPOROSIS: A REVIEW - Markovic- Temelkova, Snezana; Foteva, Marta; Stojovska Jovanovska, Elizabeta (Journal of Morphological Sciences; Vol 2 No 2 (2019): JMS, 2019)
Osteoporosis is a global pandemic affecting men and women of all ages and ethnicities. Not so long ago doctors had to rely on X- ray images for the diagnosis of osteoporosis. Dual-energy X-ray Absorptiometry (DXA) has been developed over the past half century to provide measurement of Bone Mineral Density for the purposes of clinical practice and research. BMD, measured by DXA has been the reference standard for osteoporosis diagnosis.   The trabecular bone score (TBS) is a new texture measurement that can be applied to any X-ray images including DXA images by quantifying local variations in gray level.  Lumbar spine trabecular bone score (TBS) correlates with parameters of bone microarchitecture and can predict osteoporotic fractures independently of BMD and the WHO fracture risk assessment tool (FRAX) probability. It can be applied retrospectively to an existing DXA exam without the need of any further imaging and it can be   compared directly with BMD because both evaluate  the same region of bone. The importance of TBS in bone mineral densitometry   for fracture risk assessment has been documented in a number of cross-sectional studies. We review relevant studies in order to evaluate the clinical use of this imaging tool. The clinical and scientific evidence supporting the use of TBS, makes TBS an attractive and useful clinical tool for physicians to improve patient management in osteoporosis We conclude that when used correctly, this tool provides invaluable information for the diagnosis of osteoporosis and patient management in clinical practice.